Artefoto : a ênfase fotográfica - Araújo, Laura Dias Barbosa [UNESP] (2008)
The research presented here in a form of equivalente work is an analysis of my own way of shooting with the objective of expandig the possibilities of this set of photographs, with a constant seeking of develop a particular visual language, capable of differentiating a looking in so many. The first stage of the research consisted of a ransom of my photographic production from the earliest experiences as an apprentice in 2002, until the most recent held during the Masters and, from that review, was established a criteria to systematic this work and complete the process reflexive.